Isolierte Zession bei Gesamtschulden Möglichkeit, Voraussetzungen und Rechtsfolgen der Abtretung einer Forderung gegen nur einen Gesamtschuldner - Liesenfeld, Jan (Schriften zum Bürgerlichen Recht, 2020)
»Separate Assignment of Joint and Several Debts - On the Possibility, Requirements and Consequences of an Assignment to Take Effect only against Individual Joint and Several Debtors« When claims from a joint and several debt are assigned it is often unclear, if all debtors change creditors or only some. The author clarifies this, examining accessory and ancillary rights and interpreting typical assignment contracts. He uses the structure of a joint and several debt to justify why an isolated assignment is possible and answers practical questions such as the necessity of consent from debtors or ways of performance and recourse in a joint and several debt which has been split.